FUNCTIONAL ABILITIES OF SCHOOLBOYS - TEAМ SPORTSMEN AND NONSPORTSMEN - Zoran Jonić; Marko Aleksandrović (Montenegrin Sports Academy and Faculty for Sport and Physical Education, 2006)
The goal of this research is to establish differences in some indicators of functional abilities of 5th and 6th grade students - active team sportsmen and nonsportsmen. The sample of examinees consisted of 189 fifth and sixth grade students from elementary schools of Niš. The first subsample, the group of sportsmen, consisted of 93 students, active team sportsmenyears-long (water polo, basketball, volleyball, football and team handball). Another subsample, the group of nonsportsmen, consisted of 96 students never active in sport. The assessment of functional abilities was carried out through seven variables: pulse in a state of rest, systolic blood pressure, diastolic blood pressure, imposed vital capacity, imposed expiratory volume, absolute value of maximum oxygen consumption and relative value of maximum oxygen consumption. By means of canonical discriminative analysis it is established that there are global differences between two subsamples in favor of team sportsmen.